1995
DOI: 10.1051/lait:199516
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of nisin and moderate heat on destruction of Listeria monocytogenes in milk

Abstract: Summary -The kinetics of destruction of two strains of L monocytogenes in skim milk heated at60°C with and without addition of 25 or 50 lU/mi of nisin were studied. The survival curves displayed an initiallag phase followed by an accelerating killing phase. As both the length of the lag phase and the destruction rate depended on the temperature and the presence of nisin, a mathematical model was necessary to compare the survival curves and to determine the time to achieve a given reduction of the Listeria coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 35 publications
4
8
0
1
Order By: Relevance
“…In starving P. frisingensis cells, combined effect of pH and temperature led to a strong K + release by the cells, the highest K + leaks were measured when pH was 6·2 and temperature was 50 °C, whatever the nisin level addition. This was in agreement with what was reported by Maisnier‐Patin et al . (1995), who showed that a combination of heat treatment and nisin could either enhance bactericidal action of nisin, or increase susceptibility of bacteria to the bacteriocin.…”
Section: Discussionsupporting
confidence: 94%
“…In starving P. frisingensis cells, combined effect of pH and temperature led to a strong K + release by the cells, the highest K + leaks were measured when pH was 6·2 and temperature was 50 °C, whatever the nisin level addition. This was in agreement with what was reported by Maisnier‐Patin et al . (1995), who showed that a combination of heat treatment and nisin could either enhance bactericidal action of nisin, or increase susceptibility of bacteria to the bacteriocin.…”
Section: Discussionsupporting
confidence: 94%
“…No data are reported in the literature for effect of stage of addition of turmeric on extending the shelf life of paneer. However, similar observations were made by Hurst (1981) and Maisnier-Patin et al (1995) in case of nisin, wherein better action of nisin is reported in reducing the growth of bacteria when it was used in combination with heat treatment. According to Maisnier-Patin et al (1995) nisin enhances the effect of moderate heat and had a greater effect when used along with heat.…”
Section: Effect Of Stage Of Addition Of Turmeric On Changes In Sensorsupporting
confidence: 76%
“…However, similar observations were made by Hurst (1981) and Maisnier-Patin et al (1995) in case of nisin, wherein better action of nisin is reported in reducing the growth of bacteria when it was used in combination with heat treatment. According to Maisnier-Patin et al (1995) nisin enhances the effect of moderate heat and had a greater effect when used along with heat. Taking into account that the mode of action of nisin involves pore formation in the cell membrane, the dramatic increase in thermal destruction of bacteria in the presence of nisin can be attributed to a synergistic effect of heat and nisin on the membrane damage, leading to rapid efflux of cytoplasmic constituents viz., ATP, amino acids, potassium, etc.…”
Section: Effect Of Stage Of Addition Of Turmeric On Changes In Sensorsupporting
confidence: 76%
“…The most susceptible individuals are expectant mothers, the very young with developing immune systems, and elderly and/or levels, and presence of inhibitors (Doyle et al, 2001). The heat resistance of L. monocytogenes in foods increases with fat levels (MacDonald and Sutherland, 1993), pH (Juneja and Eblen, 1999), salt content (Juneja and Eblen, 1999), and absence of antimicrobials (Maisnier-Patin et al, 1995). The special properties of a specific food may help protect L. monocytogenes against heat lethality.…”
Section: Introductionmentioning
confidence: 99%